Effects of distilled Cultivated Wild Ginseng Herbal Acupuncture in Rats with Diabetes Induced by High Fat Diet - Won Pil Park; Ki Rok Kwon; Eun Lee (Korean Pharmacopuncture Institute, 2005)
Objectives : This study was to verify the effects of distilled cultivated wild ginseng herbal acupuncture(CWGHA) on diabetes by hematological analysis. Methods : Rats were fed with high fat diet for 8 weeks and the rats with hyperglycemia were selected for the experiment. Various treatments of distilled cultivated wild ginseng herbal acupuncture were administered intravenously and glucose, β-lipoprotein, triglyceride, total-cholesterol, HDL-cholesterol, LDL-cholesterol, Free Fatty acid(FFA), TBARS, superoxide dismutase(SOD), catalase, and glutathione peroxidase activities in the liver were analyzed. Results : 1. Experiment group 3(0.1㎖ of CWGHA was injected intravenously 10 times) showed significant decrease in serum glucose, β-lipoprotein, triglyceride, LDL-cholesterol levels and liver TBARS compared to the control group, whileas showed significant increase in liver glutathione peroxidase activity. 2. Experiment group 2 and 3 (treated with 0.5㎖, 1㎖, respectively), showed significant decrease in serum FFA, total cholesterol and TBARS levels compared to the control group, and showed significant increase in liver superoxide dismutase and catalase activities. 3. Serum HDL-cholesterol didn't show significant changes in both experiment and control groups. Conclusion : Above results indicate that distilled cultivated wild ginseng herbal acupuncture plays significant role as a hypoglycemic agent and in lipid metabolism. Increase in the number of administrations yielded more significant results.